An Infectious Bursal Disease Virus (IBDV) Reverse Genetics Rescue System and Neutralization Assay in Chicken B Cells. Issue 1 (9th January 2023) - Reddy, Vishwanatha R. A. P.; Nazki, Salik; Asfor, Amin; Broadbent, Andrew J.
Abstract: Infectious bursal disease virus (IBDV) is a major threat to the productivity of the poultry industry due to morbidity, mortality, and immunosuppression that exacerbates secondary infections and reduces the efficacy of vaccination programs. Field strains of IBDV have a preferred tropism for chicken B cells, the majority of which reside in the bursa of Fabricius (BF). IBDV adaptation to adherent cell culture is associated with mutations altering amino acids in the hypervariable region (HVR) of the capsid protein, which affects immunogenicity and virulence. Until recently, this has limited both the application of reverse genetics systems for engineering molecular clones, and the use of in vitro neutralization assays, to cell‐culture‐adapted strains of IBDV. Here, we describe the rescue of molecular clones of IBDV containing the HVR from diverse field strains, along with a neutralization assay to quantify antibody responses against the rescued viruses, both using chicken B cells. These methods are readily adaptable to any laboratory with molecular biology expertise and negate the need to obtain wild‐type strains. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : A chicken B‐cell rescue system for IBDV Basic Protocol 2 : A chicken B‐cell neutralization assay for IBDV